Perancangan Aplikasi Akademik Pe Perancangan Aplikasi Akademik Pembayaran Sumbangan Pembinaan Pendidikan Menggunakan Metode User Centered Design (UCD): Perancangan Aplikasi Akademik Pembayaran Sumbangan Pembinaan Pendidikan Menggunakan Metode User Centered Design (UCD) - Sanjaya_Sjy, M rudi sanjaya Sanjaya; Lestari Ruskan, Endang; Wijaya Putra, Bayu; Arrijal Ismail, Ahmad; Izzatul Maula, Nurly; Saputra, Ariansyah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Abstract Technology is developing from year to year, so technology is needed in the form of an application, one of which is to simplify the academic administration process, one of which is designing an application for paying SPP donations (Payment of Academic Development Contributions). The design of this application aims to simplify the administration part for paying Educational Development Contributions (SPP). The research method uses interviews, observation and literature studies, then the method uses (User Centered Design) which consists of context analysis, defining requirements, design, evaluation. The design of this application is tested with the level of efficiency using the user centered design method. (UCD), The results of validity testing for the design of Educational Development Contribution (SPP) payment applications, where the efficient levels were obtained were (1) 0.646, (2) 0.772, (3) 0.595, (4) 0.853, (5) 0.514, ( 6) 0.831, (7) 0.554, (8) 0.872, (9) 0.62, (1) 0.852 stated that the efficiency level is valid. The results of reliability testing for designing the Education Development Contribution (SPP) payment application, where the efficient level is obtained is ( 1) 0.887, (2) 0.878, (3) 0.889, (4) 0.872, (5) 0.894, (6) 0.873, (7) 0.895, (8) 0.868, (9) 0.888, (10) 0.893 declared Level efficiency is declared Reliable, where the test Keywords— Aplication, Design Website, UCD, Validitas, Realibilitas.